Process improvement in a cancer outpatient chemotherapy unit using lean healthcare - Coelho, Stela Maris [UNESP]; Pinto, Carlos Frederico [UNESP]; Calado, Robisom Damasceno [UNESP]; Silva, Messias Borges [UNESP] (Elsevier, 2013)
The Instituto de Oncologia do Vale Medical Oncology Unit at Hospital Regional do Vale do Paraiba faced significant growth over the last two years. Unbalanced treatment scheduling and overcrowding is a common problem for cancer centers in Brazil, with huge access restrictions due to system inefficiencies and poor assistance design. The purpose of this report is to show how lean thinking can be applied to healthcare by using lean methods and production leveling. The case study/report presented was adopted in order to describe the approach, techniques and findings of this project, as part of a lean initiative. Lean Value Stream Mapping tools and leveling tools improved the unit performance by increasing unit capacity freeing treatment slots by leveling and length of chemotherapy application optimization. The process redesign also eliminated unnecessary movement and overtime. © IFAC.
Keywords: Lean Manufacturing; Production Control; Queues.